Innovation topics under debate at the EC: the opinions of Italian entrepreneurs, academics and policy makers. (26th May 2009) - Massa, Silvia; Testa, Stefania
This paper compares the findings of a research project aimed at investigating different perspectives on innovation issues to some of the latest, most relevant topics related to small and medium enterprise (SME) innovation under investigation in the European Commission (EC). According to recently published EC documents on the relaunched and revised Lisbon Agenda, the debate seems to focus mainly on four broad 'hot' topics: 1) What are the different dimensions of innovation and the new areas where indicators could be introduced for a better measurement of innovation? 2) How can the European Union (EU) be made more innovation friendly? 3) How can a more comprehensive intellectual property rights (IPR) strategy be developed? 4) What is the best policy to improve the interaction in and between education, research and industry? What are the challenges for the renewal of clusters and intermediaries?